2005
DOI: 10.1182/blood-2004-06-2364
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tolerance using Fas ligand: a double-edged immunomodulator

Abstract: Fas/FasL system and immune homeostasisThe immune system functions in complex and dynamic microenvironments, where decisions pertaining to the survival and/or physical elimination of antigen-specific T-cell clones are critical to the establishment and maintenance of functional immunity. Activationinduced cell death (AICD) is the primary homeostatic mechanism used by the immune system to control T-cell responses, promote tolerance to self-antigens, and prevent autoimmunity. [1][2][3] Following activation, T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 120 publications
(189 reference statements)
1
104
0
Order By: Relevance
“…Earlier studies indicated that the membrane bound FasL may be released from cell surface after protease-mediated cleavage and the soluble form may act as a chemotactic factor that induces the migration of neutrophils. 3,22 In contrast, we have found that soluble form of FasL did not trigger apparent inflammation or tumor rejection. 23 A recent study provided evidence that FasL-triggered inflammation correlated with its cytotoxic activity and was in fact a secondary effect of the locally induced apoptosis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Earlier studies indicated that the membrane bound FasL may be released from cell surface after protease-mediated cleavage and the soluble form may act as a chemotactic factor that induces the migration of neutrophils. 3,22 In contrast, we have found that soluble form of FasL did not trigger apparent inflammation or tumor rejection. 23 A recent study provided evidence that FasL-triggered inflammation correlated with its cytotoxic activity and was in fact a secondary effect of the locally induced apoptosis.…”
Section: Discussionmentioning
confidence: 80%
“…[1][2][3] FasL is expressed in the eye and testis where its pro-apoptotic activity, along with a variety of other immunosuppressive factors, is considered to contribute to the immune privilege status of these tissues. [3][4][5][6] FasL is also expressed by many human tumors and is associated with poor prognosis in breast, 7,8 ovarian 9 and liver 10 cancers, leading to the hypothesis that tumors use FasL to counterattack the tumorinfiltrating cytotoxic T cells and to escape the immune clearance. 11,12 In contrast to these observations, tumor cells engineered to express exogenous FasL triggered a potent neutrophil-mediated local inflammatory response and were rapidly rejected.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Systemic immunomodulation by CD95L was successfully achieved by antigen-presenting cells modified to express CD95L. 13 In mice antigen-specific elimination of activated T cells by engagement of CD95L on APC and CD95 on the activated T cells has been demonstrated in several models. 14,15 This approach benefits from the high specificity since only T cells responding to the antigen expressed on the APC are deleted by CD95/CD95L interaction while the remaining T cells are still responsive to unrelated antigens.…”
mentioning
confidence: 99%
“…35,36 Fas-L mediated T-lymphocyte apoptosis in immune privileged sites might protect the tissue/site from immune damage, thereby inducing immune tolerance. 37 In other studies Fas-L protein has been implemented in the reduction of allogenic rejection independent of apoptotic induction. 38,39 In our study, the Fas-L protein was upregulated by both the host and injected cells following transplantation, especially at day 10 when CD34 À cells were used.…”
mentioning
confidence: 99%